Evaluating The Effectiveness Of Government Policies In Addressing Climate Change Challenges For Farmers In Marathwada - Siddiqui, Ms. Tayyaba; Mahajan, Dr. D. J. (South Eastern European Journal of Public Health, 2025)
This research paper evaluates the effectiveness of government policies designed to address climate change challenges farmers face in the Marathwada region of Maharashtra. It explores how well these policies are communicated, their integration with traditional farming practices, and the role of local communities and NGOs in their implementation. The paper assesses the accessibility and impact of policies such as the Soil Health Card Scheme and other state and national-level agricultural support initiatives, providing insights into barriers faced by farmers in accessing these benefits. Additionally, it highlights how effective communication between farmers and authorities can enhance policy effectiveness in combating climate change.